2014
DOI: 10.1111/1556-4029.12522
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Electron Microscope Analysis of Gunshot Defects to Bone: An Underutilized Source of Information on Ballistic Trauma

Abstract: Recent years have seen increasing involvement by forensic anthropologists in the interpretation of skeletal trauma. With regard to ballistic injuries, there is now a large literature detailing gross features of such trauma; however, less attention has been given to microscopic characteristics. This article presents analysis of experimentally induced gunshot trauma in animal bone (Bos taurus scapulae) using full metal jacket (FMJ), soft point (SP), and captive bolt projectiles. The results were examined using s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 55 publications
1
25
0
Order By: Relevance
“…A forensic anthropologist or pathologist would be able to look at the size of the entrance wound, the presence of lead on the margins of the wound, and the presence or absence of cortical flaking to approach the question of the size and type of bullet used to inflict that wound. We are in agreement with the conclusion that SEM analysis is underutilized in the analysis of ballistic trauma (28). This research lends itself to the now more focused description of ammunition used during the search and seizure of evidence.…”
Section: Bullet Type Estimationsupporting
confidence: 89%
See 1 more Smart Citation
“…A forensic anthropologist or pathologist would be able to look at the size of the entrance wound, the presence of lead on the margins of the wound, and the presence or absence of cortical flaking to approach the question of the size and type of bullet used to inflict that wound. We are in agreement with the conclusion that SEM analysis is underutilized in the analysis of ballistic trauma (28). This research lends itself to the now more focused description of ammunition used during the search and seizure of evidence.…”
Section: Bullet Type Estimationsupporting
confidence: 89%
“…Therefore, the presence of cortical flaking is associated with trauma on bone from a copper bullet, while the absence of flaking is indicative of a bullet made of lead. The characteristics of bullet wound morphology from full metal jacket bullets are supported by Rickman and Smith's research .…”
Section: Resultsmentioning
confidence: 68%
“…The work detailed in the current paper is part of a wider suite of ballistic experiments with relevance to Forensic Anthropology. One of these parallel projects [6] utilized cattle (Bos taurus) scapulae as proxies for human cranial bone in considering microscopic effects of gunshot trauma. Here fresh scapulae obtained from an abattoir from animals that had been slaughtered for food, were shot with minimal soft tissue (<5mm thick) adhering.…”
Section: Experimental Conditions and Samplesmentioning
confidence: 99%
“…Further, the microstructure of bone has been shown to influence its response to ballistic trauma in complex ways at a microscopic level, including delamination, directional cortical bending and lateral deflection of portions of cortex. It has been demonstrated that such changes are recognizable to the extent that they can be used to differentiate between different types of ammunition microscopically [6]. In contrast to this organized complexity, polyurethane has an essentially uniform microstructure devoid of regular organization above the molecular level.…”
Section: The Devil In the Detailmentioning
confidence: 99%
“…Weapons with a high velocity can also produce extensive fractures. The nature of this type of injury implies lethal intent (Lambert, 1997:90;Rickman and Smith, 2014).…”
Section: Identifying Cranial Traumamentioning
confidence: 99%